Arabidopsis plants exposed to gamma radiation in two successive generations show a different oxidative stress response. (December 2016) - van de Walle, Jorden; Horemans, Nele; Saenen, Eline; Van Hees, May; Wannijn, Jean; Nauts, Robin; van Gompel, Axel; Vangronsveld, Jaco; Vandenhove, Hildegarde; Cuypers, Ann
Abstract: When terrestrial environments get contaminated with long-lived gamma emitting radionuclides, plants that grow in these contaminated areas are exposed to gamma radiation during consecutive generations. Therefore it is important to evaluate the gamma induced stress response in plants in and between generations. The objective of this research is to reveal differences at the level of the antioxidative stress response between generations with a different radiation history. An experiment was conducted in which 7-days old Arabidopsis thaliana plants were exposed for 14 days to four different gamma dose rates: 22 mGy/h, 38 mGy/h, 86 mGy/h and 457 mGy/h. Two different plant groups were used: plants that were not exposed to gamma radiation before (P0) and plants that received the aforementioned gamma treatment during their previous generation (S1). Growth, the concentration of the antioxidants ascorbate and glutathione, a number of antioxidative enzyme activities and their gene transcript levels were analysed. A dose-rate dependent induction was seen for catalase (CAT) and guaiacol peroxidase (GPX) in the roots and for syringaldazine peroxidase (SPX) in the shoots. Differences between the two generations were observed for CAT and GPX in the roots, where a significantly higher activity of these reactive oxygen species (ROS) detoxifying enzymes was observed in the S1 generation. For SPX in the shoots, a dose dependent upregulation was observed in the P0 generation. However, high SPX activities were present for all doses in the S1 generation. These differences in enzyme activity between generations for SPX and GPX and the involvement of these enzymes in cell wall biosynthesis, suggest an important role for cell wall strengthening in the response to gamma irradiation. Highlights: Positive but transient effect of gamma stress on growth of Arabidopsis thaliana in both generations. Stronger antioxidative response to gamma exposure in second generation. Differences between generations for enzymes involved in cell wall metabolism.